Preparation and characterization of a stereocomplex of poly(lactide-co-epsilon-caprolactone)/tricalcium phosphate biocomposite using supercritical fluid technology - Nurqadar, R. I.; Purnama, P.; Kim, S. H. (BUDAPEST UNIV TECHNOL & ECON, 2013)
A novel biocomposite material from a stereocomplex of poly (L-lactide-co-epsilon-caprolactone) (PLLCL) and poly (D-lactide-co-epsilon-caprolactone) (PDLCL) and inorganic tricalcium phosphate (TCP) was prepared by supercritical fluid method. Both pristine and poly (L-lactide)-grafted-TCP (PLLA-g-TCP) were used. PLLA-g-TCP was produced by ringopening polymerization of L-lactide in the presence of surface-activated Tcp. Infrared (IR) spectroscopy and scanning electron microscopic (SEM) images confirm the attachment of PLLA onto the activated TCP surface. The stereocomplex formation of biocoinposite was confirmed by differential scanning calorimetry (DSC) and wide-angle X-ray diffraction (WAXD). The biocomposite containing PLLA-g-TCP has higher stereocomplex degree and more homogeneous TCP distribution compared to the biocomposite containing pristine Tcp. The presence of PLLA-g-TCP in the stereocoinplex PLLCL-PDLCL (s-PDLCL) enhance the stereocomplex degree up to a certain content and also supports the -homogeneous TcP dispersion in the stereocoinplex matrix. These phenomena support the improvement in mechanical properties of the s-PDLCL composite the optimum content of PLLA-g-TCP being 10,/o. The biocomposites containing TCP materials are promising materials for biomedical application, especially for bone tissue engineering.
Keywords: IN-VITRO BIOACTIVITY; TRICALCIUM PHOSPHATE; COMPOSITE; SURFACE; BONE